1977
DOI: 10.1001/archderm.113.5.627
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal vascular reactions in atopic dermatitis

Abstract: Vascular reactions to mechanical stroking, topical application of nicotinic acid ester, and methacholine chloride were examined in both the normal and abnormal skin of 100 patients with atopic dermatitis and 20 patients with allergic contact dermatitis. White dermographism, nicotinic acid blanching, and delayed blanch with methacholine consistently occurred in areas of skin with eczematous change of patients with atopic dermatitis and those with allergic contact dermatitis. Normal skin of atopic patients did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
2

Year Published

1980
1980
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…In other words, it became evident that atopies with dry, scaly, or lichenified AE react to dermographic pressure with only weak hyperemia in the cutaneous blood vessels, in contrast to the significantly stronger hyperemia in the non-atopic healthy controls displaying bright red D. The data obtained can well be explained by an intrinsic "throttling factor" impeding dermographically induced vasodilation in the peripheral vessels. This concept is also in accordance with the theory of active vasoconstriction in acetylcholine-induced skin blanching supported by several authors (12)(13)(14)(15).…”
supporting
confidence: 92%
“…In other words, it became evident that atopies with dry, scaly, or lichenified AE react to dermographic pressure with only weak hyperemia in the cutaneous blood vessels, in contrast to the significantly stronger hyperemia in the non-atopic healthy controls displaying bright red D. The data obtained can well be explained by an intrinsic "throttling factor" impeding dermographically induced vasodilation in the peripheral vessels. This concept is also in accordance with the theory of active vasoconstriction in acetylcholine-induced skin blanching supported by several authors (12)(13)(14)(15).…”
supporting
confidence: 92%
“…Patients with atopic dermatitis show a tendency towards vasoconstriction of the small vessels in the skin, 1 as evidenced by facial pallor, 2 cold hands and feet, 3 and vasoconstrictive reaction to mechanical or pharmacological stimuli. 4,5 As vasoconstriction in the terminal vasculature contributes to the cause of hypertension, 6 it is natural to suppose that incidence of hypertension might be higher in adult patients with atopic dermatitis, compared with normal controls.…”
mentioning
confidence: 99%
“…Perhaps the best known of these is the delayed blanch response to acetylcholine, first described by Lobitz & Campbell in 1953 (10). Subsequent studies have shown that this reaction, demonstrable in 70% of patients, probably occurs only in areas of inflammation and is not specific for AD (11). Still unresolved is the question of whether the blanching is a result of vasoconstriction or compression from dermal edema (3).…”
Section: Pharmacophysiological Abnormalitiesmentioning
confidence: 99%